ANÁLISIS DE SEIS POBLACIONES LATINOAMERICANAS DE GATOS MEDIANTE GENES DEL PELAJE Y MARCADORES MICROSATÉLITES - Ruiz García, Manuel; Alvarez, Diana (Instituto de Ecología, A.C., 2003)
Six Latin American cat populations (La Havana, San Jose, Bogotá, Asunción, Buenos Aires and Santiago) have been studied from a population genetics standpoint by using different morphological coat and molecular microsatellite markers (FCA43, FCA45, FCA96 and FCA126). The main aims of the current work are as follows: (1) To determine whether the type and intensity of the genetic differences found for diverse morphological loci among the current British cat populations and those from the British oversea colonies (USA, Canada and Australia) agree with the differences among the current Spanish cat populations and those from Latin America and (2) to determine if the genetic relationships among some of these Latin American cat populations are in agreement by using independently morphological and molecular microsatellite markers. The different results obtained were as follows: (A) All populations analyzed were in Hardy-Weinberg equilibrium at the O, S and at the four microsatellite loci studied with the exception of La Havana at the S locus. (B) The trees obtained showed that the relationships of the six cat populations studied regard to the Spanish populations, in particular, and with the European populations, in general, were extremely heterogeneous. Therefore, for instance, Asuncion was genetically identical to some Catalonian populations meanwhile Santiago (Chile) revealed more resemblance with the cat populations of presumed British origin in the Eastern Coast of the United States by means of the coat color genes. The striking genetic heterogeneity among some of these Latin American cat populations could be explained by the existence of different geographic, or temporal, migrations from Spain and/or that diverse gene drift degrees were present in the foundation of the diverse populations studied. Finally, the molecular results were similar to those obtained with the gross morphological genes. Therefore, the overall evolution of these morphological markers is controlled more probably by neutral stochastic forces than by selective ones.